2003
DOI: 10.1536/jhj.44.41
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility and Safety of Early Discharge for Low Risk Patients with Acute Myocardial Infarction after Successful Direct Percutaneous Coronary Intervention.

Abstract: SUMMARYThere is a lack of consensus among cardiologists regarding the length of time patients should be hospitalized after an uncomplicated acute myocardial infarction (AMI) and successful direct percutaneous coronary intervention (d-PCI). The purpose of this study was to evaluate the feasibility and safety of early discharge (discharge <4 days after the procedure) for low risk patients with AMI who underwent successful d-PCI.From

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…2,3,4,9) There was no study in which the average time of hospitalization was less than 72 hours. The majority of these studies dealt with patients treated with intravenous thrombolysis, 2,4) and most investigated patients who underwent coronary angiography or exercise testing before discharge from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,4,9) There was no study in which the average time of hospitalization was less than 72 hours. The majority of these studies dealt with patients treated with intravenous thrombolysis, 2,4) and most investigated patients who underwent coronary angiography or exercise testing before discharge from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Three articles presenting information about returning to work (6,10,16) , showed that patients who had early mobilization returned earlier to their jobs (12 weeks in average) when compared to those who had late Chart 3 -Studies comparing early and late hospital discharge after acute myocardial infarction (20) 1973 69 69 14 th day 21 st day Ahlmark (22) 1979 128 124 8 th day 15 th day Baughman (21) 1982 64 59 14 th day 21 st day Cheng (23) 1986 34 34 5 th day 10 th day Yip (25) 2003 266 197 <4 days >4 days Barchielli (24) 2007 115 327 3 rd and 4 th day 9 th day Chart 4 -Complications after patients with acute myocardial infarction were discharged from the hospital, articles describing them and the number of patients who had presented them again, according to early and late hospital discharge.…”
Section: Early and Late Mobilizationmentioning
confidence: 99%
“…Re-infarction Hutter (20) ; Baughman (21) Ahlmark (22) , Cheng (23) , Barchielli (24) , Yip (25) 61 (5.18%) 34 (5.51%) Angina Hutter (20) ; Baughman (21) Ahlmark (22) Cheng (23) , Yip (25) 33 (5.88%) 42 (8.64%)…”
Section: Complications Articles Describing the Complication N And % Omentioning
confidence: 99%
See 2 more Smart Citations